PENGARUH PARTISIPASI PENGANGGARAN, PENEKANAN ANGGARAN, KOMITMEN ORGANISASI, DAN KOMPLEKSITAS TUGAS TERHADAP SLACK ANGGARAN PADA BANK PERKREDITAN RAKYAT (BPR) DI KABUPATEN BADUNG - VERONICA, AMELIA; AYU KRISNADEWI, KOMANG (Jurnal Ilmiah Akuntansi dan Bisnis, 2009)
The purpose of this research is to investigate the impact of budgeting participation, budget emphasize, organization commitment, and task complexity on budgetary slack of BPR in Badung Regency simultaneously and partially. To solve the research problem, hypotheses are tested using multiple linear regressions. The result shows that budgeting participation, budget emphasize, organization commitment, and task complexity affect budgetary slack both simultaneously and partially.
Keywords: budgeting participation, budget emphasize, organization commitment, task complexity, and budgetary slack